Pregnancy outcomes following diagnosis and treatment of adolescent and young adult cancer - Haggar, F.; Preen, D.; Pereira, Gavin; Holman, D.; Einarsdottir, K. (WILEY-BLACKWELL, 2014)
Background: Improvements in cancer therapy have led to an expanding population of adolescent and young adult (AYA) cancer survivors. In contrast to childhood survivors, there is a still lack of data concerning reproductive outcomes among AYA survivors. Aim: To investigate obstetric and perinatal outcomes among female survivors of AYA cancers and their offspring. Methods: Using multivariate analysis of statewide linked data, outcomes of all first completed pregnancies (n = 1894) in female survivors of AYA cancer diagnosed in Western Australia during the period 1982–2007 were compared with those among females with no cancer history. Comparison pregnancies were matched by maternal age-group, parity and year of delivery. Results: Compared with the non-cancer group, survivors of AYA cancer had an increased risk of threatened abortion (adjusted relative risk 2.09, 95% confidence interval 1.51–2.74), gestational diabetes (2.65, 2.08–3.57), pre-eclampsia (1.32, 1.04–1.87), post-partum hemorrhage (2.83, 1.92–4.67), cesarean delivery (2.62, 2.22–3.04), and maternal postpartum hospitalization >5 days (3.01, 1.72–5.58), but no excess risk of threatened preterm delivery, antepartum hemorrhage, premature rupture of membranes, failure of labor to progress or retained placenta. Their offspring had an increased risk of premature birth (<37 weeks: 1.68, 1.21–2.08), low birth weight (<2500 g: 1.51, 1.23–2.12), fetal growth restriction (3.27, 2.45–4.56), and neonatal distress indicated by low Apgar score (<7) at 1 minute (2.83, 2.28–3.56), need for resuscitation (1.66, 1.27–2.19) or special care nursery admission (1.44, 1.13–1.78). Congenital abnormalities and perinatal deaths (intrauterine or ≤7 days of birth) were not increased among offspring. Conclusions: Survivors of AYA cancer have moderate excess risks of adverse obstetric and perinatal outcomes arising from subsequent pregnancies that may require additional surveillance or intervention.